Synopsis: Who benefits from the rapidly increasing voluntary sustainability standards? Evidence from fairtrade and organic certified coffee in Ethiopia - Minten, Bart; Dereje, Mekdim; Engida, Ermias; Tamru, Seneshaw (International Food Policy Research Institute, 2015)
Voluntary Sustainability Standards (VSS) are rapidly increasing in global value chains. While consumers, mostly in developed countries, are willing to pay significant premiums for such standards, it is not well understood how effectively these incentives are transmitted to producing countries.